-(x-3)=-x-1

Simple and best practice solution for -(x-3)=-x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x-3)=-x-1 equation:


Simplifying
-1(x + -3) = -1x + -1

Reorder the terms:
-1(-3 + x) = -1x + -1
(-3 * -1 + x * -1) = -1x + -1
(3 + -1x) = -1x + -1

Reorder the terms:
3 + -1x = -1 + -1x

Add 'x' to each side of the equation.
3 + -1x + x = -1 + -1x + x

Combine like terms: -1x + x = 0
3 + 0 = -1 + -1x + x
3 = -1 + -1x + x

Combine like terms: -1x + x = 0
3 = -1 + 0
3 = -1

Solving
3 = -1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| Q^2-16Q+28=0 | | Y-2=1/2(x-7) | | 3x-4x=-8-10 | | -7w+4(w+6)=27 | | X-235=237 | | Y-7=4/5x | | -18=1/3a-16 | | 219+x=540 | | -5=mx+b | | X-2/3=5/12 | | (27x^6-12x^5)/(3x^2) | | 7x=567 | | -7(3x-4)-(2x-3)=15x-(-4x+20) | | 14x=476 | | 2/7*49 | | Y=m(-5)+b | | 250-x=25 | | b=(4*a)-3 | | 4xy=64 | | PX+387=628 | | 9q+8=-4 | | 325*225= | | 2x+y=5y-4x | | C/20-41 | | X-189=165 | | -35x=-21 | | 6e^2x=42 | | -4m+3= | | N=10-3/8 | | 3(9x+12)+(-2x+5)= | | 4(y+3)-3=41 | | 5h-7= |

Equations solver categories